A point with pointsification? clarifying and separating pointsification from gamification in education - Hellberg, Ann-Sofie; Moll, Jonas (Frontiers in Education, 2023)
Gamification gained popularity in the 2010s, with educational professionals quickly adopting it as a way to transfer the motivational effects of games to a learning situation. However, the rapid implementation of gamification without proper planning led to a misunderstanding of the concept, namely that the use of points and rewards is enough. Proper gamification in education requires careful planning and a game-thinking approach to the design of the learning environment. The simple addition of points and badges is therefore a misuse of the gamification concept, which has been referred to as pointsification. This misuse leads to confusion and mixed results as studies using pointsification are often still labelled as gamification. This paper clarifies the differences and uses of gamification and pointsification by analyzing the effects of pointsification in a higher education course and discussing these effects in relation to gamification. The research employs a mixed methods approach, examining project grades, individual grades, and students' opinions. The objective is to show how pointsification can be implemented in education to lead to better learning in a way that both prevents previously identified problems associated with pointsification and also addresses them effectively. Although the use of points and badges has received criticism, studies have also demonstrated that pointsification can improve student engagement and motivation. As such, pointsification should be considered a distinct concept that focuses solely on the use of points and rewards to motivate students, while gamification should encompass a broader game-thinking approach.